The politics of Piketty: what political science can learn from, and contribute to, the debate on Capital in the Twenty-First Century - Hopkin, Jonathan (The British Journal of Sociology, 2014)
Thomas Piketty's imposing volume has brought serious economics firmly into the mainstream of public debate on inequality, yet political science has been mostly absent from this debate. This article argues that political science has an essential contribution to make to this debate, and that Piketty's important and powerful book lacks a clear political theory. It develops this argument by first assessing and critiquing the changing nature of political science and its account of contemporary capitalism, and then suggesting how Piketty's thesis can be complemented, extended and challenged by focusing on the ways in which politics and collective action shape the economy and the distribution of income and wealth. Although Capital's principal message is that ‘capital is back’ and that without political interventions active political interventions will continue to grow, a political economy perspective would suggest another rather more fundamental critique: the very economic forces Piketty describes are embedded in institutional arrangements which can only be properly understood as political phenomena. In a sense capital itself – the central concept of the book – is almost meaningless without proper consideration of its political foundations. Even if the fact of capital accumulation may respond to an economic logic, the process is embedded in a very political logic. The examples of housing policy and the regulation, and failure to regulate, financial markets are used to illustrate these points.
Keywords: capital; inequality; institutions; political science

Towards a Polanyian Sociology - Gemici, Kurtuluş (European Journal of Sociology, 2014)
Keywords: BLOCK, Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; anthropology; nonfiction; review

Capital in the Twenty-First Century by Thomas Piketty translated by Arthur Goldhammer (Cambridge, MA, Harvard University Press, 2014) - Milkman, Ruth (European Journal of Sociology / Archives Européennes de Sociologie, 2014)
KM - A book review of Capital in the Twenty-First Century that points out the glaring omission of Polanyi.
Keywords: Great Transformation, The (Book); PIKETTY, Thomas; book review

Polanyian Themes: From Budapest to the Caribbean - Block, Fred (Development & Change, 2014)
KM: Book review of "From the Great Transformation to the Great Financialization"
Keywords: FROM the Great Transformation to the Great Financialization (Book); From the Great Transformation to the Great Financialization (Book); LEVITT, Kari, 1923-; POLANYI LEVITT, Kari; economic development; nonfiction

Karl Polanyi: New Perspectives on the Place of the Economy in Society - Harvey, Mark; Ramlogan, Ronnie; Randles, Sally (Oxford University Press, 2014)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology and social policy. Newly available in paperback, this volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations and European labour markets.
Keywords: business & economics; economic theory

Income Inequality in Advanced Capitalism: How Protective Institutions can Promote Egalitarian Societies - Kollmeyer, Christopher (Comparative Sociology, 2014)
This study develops a Polanyian perspective on income inequality in advanced capitalist countries. Polanyi's historical account of the rise and fall of classic liberalism in Britain illustrated how social groups and society at large devised "protective institutions" to shield themselves from socially destructive market forces. Recent qualitative applications of this idea identify three protective institutions as being the most important - the public sector economy, trade unions, and the family. Using data from 16 Western countries from 1970 to 2010, this study demonstrates that cross-national and temporal variations in these protective institutions explain a considerable amount of the observed patterns of income inequality among these countries, helping to explain why some countries have recently experienced rising inequality but others have not. The study ends by arguing that a Polanyian perspective provides more analytical and theoretical leverage than other sociological approaches to understanding income inequality.
Keywords: The Great U-Turn; capitalism; economic sociology; income distribution; income inequality; labor unions; labour unions; liberalism; protective institutions; research; social groups - research

Informalizing the Economy: The Return of the Social Question at a Global Level - Breman, Jan; van der Linden, Marcel (Development and Change, 2014)
The classical conceptualization of the working class, of workers’ collective action and, especially, of trade unionism, was implicitly or explicitly based on the Standard Employment Relationship that, for a few decades, has been dominant in North America, Europe, Japan and Australasia. The ‘classical’ model of collective bargaining, which has shaped the world's traditional labour movements, was based on this conceptualization. However, it is now increasingly undermined by the rapid spread of ‘informal’ or ‘precarious’ labour in the global North. It is our contention that the ‘classical’ view of the working class and workers’ collective action is fundamentally biased and takes as a norm or standard what was in fact an historical exception. The real norm or standard in global capitalism is insecurity, informality or precariousness, and the Standard Employment Relationship is an historical phenomenon which had a deep impact in a limited part of the world for a relatively short period of time. If, as we argue, the ‘Rest’ is not now becoming like the ‘West’, but the other way round, then the ‘traditional’ forms of collective action that have developed in the North Atlantic region during the last two centuries are gradually losing much of their impact. New forms of collective action are emerging, though these are often still at an embryonic stage. It is, therefore, high time to rethink the concept of the working class and the ways in which it can further its interests.
Keywords: informalization; precarity

Alienated Politics: Labour Insurgency and the Paternalistic State in China - Friedman, Eli (Development and Change, 2014)
Is there a labour movement in China? This contribution argues that China does not have a labour movement, but that contestation between workers, state and capital is best characterized as a form of ‘alienated politics’. Widespread worker resistance is highly effective at the level of the firm because of its ability to inflict losses on capital and disrupt public order. But authoritarian politics in China prevent workers from formulating political demands. Despite the spectacular repressive capacity of the state, the central government has in fact responded to highly localized resistance by passing generally pro-labour legislation over the past decade. The consequence of this is that worker unrest has produced important political shifts at the national level, but these have come about without workers’ direct involvement in the process. In other words, workers are alienated from the political object that they themselves have produced. As a consequence, when the state intervenes in labour politics, it appears to be doing so of its own accord, i.e. paternalistically. This framework helps us to understand how worker unrest in China has become highly antagonistic towards employers and the local state, while maintaining the stability of the system as a whole.
Keywords: China; alienated politics; labor movement; labour movement; paternalistic state

The Food-Energy-Climate Change Trilemma: Toward a Socio-Economic Analysis - Harvey, Mark (Theory, Culture & Society, 2014)
The food-energy-climate change trilemma refers to the stark alternatives presented by the need to feed a world population growing to nine billion, the attendant risks of land conversion and use for global climate change, and the way these are interconnected with the energy crisis arising from the depletion of oil. Theorizing the interactions between political economies and their related natural environments, in terms of both finitudes of resources and generation of greenhouse gases, presents a major challenge to social sciences. Approaches from classical political economy, transition theory, economic geography, and political ecology, are reviewed before elaborating the neo-Polanyian approach adopted here. The case of Brazil, analysed with an `instituted economic process’ framework, demonstrates how the trilemma is a spatial and historical socio-economic phenomenon, varying significantly in its dynamics in different environmental and resource contexts. The paper concludes by highlighting challenges to developing a social scientific theory in this field.
Keywords: climate change; climatic changes; economic geography; energy consumption; energy shortages; food consumption; food security; instituted economic process; limits to growth; peak oil; political ecology; socioeconomics; sociogenesis

Making Capitalism Fit For Society - Crouch, Colin (John Wiley & Sons, 2014)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies. Can capitalism be reshaped so that it is fit for society, or must we acquiesce to the neoliberal view that society will be at its best when markets are given free rein in all areas of life? The aim of this book is to show that the acceptance of capitalism and the market does not require us to accept the full neoliberal agenda of unrestrained markets, insecurity in our working lives, and neglect of the environment and of public services. In particular, it should not mean supporting the growing dominance of public life by corporate wealth. The world’s most successful mature economies are those that fully embrace both the discipline of the market and the need for protection against its negative outcomes. Indeed, a continuing, unresolved clash between these two forces is itself a major source of vitality and innovation for economy and society. But maintenance of that tension depends on the enduring strength of trade unions and other critical groups in civil society - a strength that is threatened by neoliberalism’s increasingly intolerant onward march. Outlining the principles for a renewed and more assertive social democracy, this timely and important book shows that real possibilities exist to create a better world than that which is being offered by the wealthy elites who dominate our public and private lives.
Keywords: business & economics; capitalism; economic theory

Penser la pluralité des monnaies à partir de Polanyi : un essai de typologie - Blanc, Jérôme (ERES, 2014)
A large number of currencies has emerged for thirty years, far beyond the national currencies alone. It includes systems created by groups of citizens, others by territorial communities, and others by private companies for their own benefit. These currencies take various forms, ranging from electronic money on smart cards to settlement systems ...
Keywords: currencies; modern currencies

Maintenir l'ordre économique, Maintaining the economic order - Gayon, Vincent; Lemoine, Benjamin (Politix, 2014)
La sociologie des politiques économiques défendue dans cet article prend pour objet le travail permanent de construction, de naturalisation et de maintien de l’ordre économique déployé par une multitude d’acteurs et d’instruments techniques. Il s’agit d’ouvrir des enquêtes sur la façon dont prennent forme les processus de désencastrement et de réencastrement de l’économie vis-à-vis des institutions politiques et sociales. Cette piste est suivie en quatre temps. D’abord en soulignant la portée sociogénétique de l’œuvre de Karl Polanyi et son insistance sur l’émancipation disputée et incertaine des pratiques de production et d’échange à l’égard des tutelles traditionnelles. Puis en montrant comment l’invention de l’économie en tant que sphère d’activité autonome suscite foule de résistances et de « mondes économiques renversés », opposant leurs propres normes aux « lois » supposées de l’économie. La configuration de l’après Seconde Guerre mondiale est revisitée comme un laboratoire exemplaire de réencastrement politico-étatique de l’économie. Le désencastrement néolibéral des marchés financiers à l’échelle internationale recompose ensuite les comptes de la puissance publique et privée. Ces ordres économiques balisent simultanément des zones d’accès et, réciproquement, de non-droit à la discussion publique et politique., ENG: The sociology of economic policies argued in this article investigates the permanent work of construction, naturalization and maintenance of the economic order made by a multitude of actors and technical instruments. It consists in describing how the doctrinal project of economy disembeddedness takes shape, detaching itself from the political and social institutions. This program is developed through four steps. First, by offering a constructivist reading of Karl Polanyi writings and highlighting the author’s insistence on the uncertain and contested process of production and exchanges’ practices emancipation vis-à-vis traditional guardianship. Then, by showing how the invention of the economy as an autonomous sphere of activity raises crowd resistance and « reversed economic worlds » settling their own standards and laws by opposition to the economy « rules » and values. The after World War Two configuration is revisited as an exemplary laboratory of Politics and State re-embeddedness of the economy. Then, neoliberal disembeddedness of global capital markets reshapes accounts of public and private powers. These economic orders simultaneously mark out areas of access to and, conversely, of non-entitlement to public and political discussion.
Keywords: constructivist; embeddedness

Spatial egalitarianism as a social ‘counter-movement’: on socio-economic reforms in Chongqing - Lim, Kean Fan (Economy & Society, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million m2of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely (i) the caste-like categorization of populations according to ‘urban’ and ‘rural’; and (ii) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ‘counter-movement’ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.
Keywords: China; Chongqing; double movement; economic reform; equality; hukou; public welfare; social change; spatial egalitarianism; state–market relations; substantivist; urban–rural integration

Communication Policy and the "Double Movement" - Ashley, Seth (Javnost-The Public, 2014)
Karl Polanyi's concept of a "double movement" has been used to describe the protectionist measures taken by governments to mitigate damage caused by the expansion of markets. Through a lens of political economy and historical institutionalism, this article uses Polanyi's framework to examine competing notions of the public interest as exemplified by the socially constructed nature of American and British broadcasting and the legitimating discourse that produced divergent outcomes. A historical analysis points to a decline of the double movement in communication policy, particularly in the U.S., and lends support to calls for noncommercial, public media structures and increased regulation of communication industries.
Keywords: communication policy; double movement; economic research; institutionalism (religion); marketing research; media system structure; protectionism

Can productivity be socially embedded? Reflections on some productivity measures of 2000s - Kocer, Ruya Gokhan (International Journal of Productivity & Performance Management, 2014)
Purpose – The purpose of this paper is to give an overview of items that are included in recent productivity programmes in various countries and integrate these items with the ideas of virtuous circuit of productivity and socially embedded productivity. Design/methodology/approach – In depth analysis of an illustrative set of productivity measures. The analysis reveals how each measure/programme could make sense to the industrial relations actors. A new conceptual reformulation of analysed measures and programmes. Findings – Bilateral productivity deals between trade unions and employers are not necessarily good from the perspective of national policy making. For this kind of uncoordinated productivity measures, though may be good for individual enterprises, may increase unemployment by pushing other domestic competitors out of the market or compelling them to lay-off workers in a reactive fashion. By drawing on Polanyi, one may argue that it is possible to strike a good balance between productivity concerns and societal interests by embedding the former into the latter. Research limitations/implications – The purpose is to introduce a new conceptualization, thus the empirical material is meant to be illustrative rather than extensive. Originality/value – By using graphical displays and empirical argumentation two new concepts are introduced: first, virtuous circuit of productivity and second, socially embedded productivity.
Keywords: employees; employers; industrial relations research; labor productivity; labor unions; labour productivity; labour relations; labour unions; productivity; research; social embeddedness; social partners

Living permanent liminality: the recent transition experience in Ireland - Szakolczai, Arpad (Irish Journal of Sociology, 2014)
Modernity, or the combination of market economy, liberal democratic polity and a society driven by technological progress, we are led to believe, is the end-state of history; the glorious condition of a fully enlightened society of free citizens equipped with equal rights at which all traditional societies are bound to arrive, after a period of transition which might involve some temporary difficulties or 'sacrifices'. However, and in contrast to this, modernity rather involves an infinite period of transition, in which the stable elements of social life, representing not just rigid external constraints on individual freedom, but also the condition of possibility of meaningful life, are one by one liquidated. This article argues that the anthropological concept 'liminality' is particularly helpful in understanding the formative aspects of transition experiences, like the Celtic Tiger phenomenon in Ireland. It also helps to move beyond the conventional 'transition to modernity' framework by pointing out that advanced modernity is identical to a permanent state of transitionality.
Keywords: FOUCAULT, Michel, 1926-1984; Ireland; POLANYI, Karl, 1886-1964; capitalism; genealogy; liminality; manners & customs; modern society; modernity; technological innovations & economics; tradition; trickster

Different Meanings of ‘Knowledge as Commodity’ in the Context of Higher Education - Kauppinen, Ilkka (Critical Sociology (Sage Publications, Ltd.), 2014)
Commodification has been and still is one of the key processes within capitalist market economies. Since the 1970s, different forms of knowledge have increasingly been subjected to this process. In this paper the commodification of knowledge in the field of higher education is defined in a broad sense as an example of the intensive enlargement of capitalism. I argue that knowledge shares some features of public goods and can be subjected to commodification both as an educational product and academic research itself. However, the simple dichotomy of public vs. private good is not nuanced enough to understand the status of knowledge within higher education. How to reconstruct this dichotomy, whether knowledge should be commodified, and how to justify one’s normative stance in this respect are three important issues for further study.
Keywords: academic capitalism; capitalism; capitalists & financiers; commodification; commodification of knowledge; commodity; higher education; knowledge; public goods

Cartographie des échanges - Steiner, Philippe (Nouvelles Perspectives en Sciences Sociales, 2014)
In this article, I examine the main typologies of transaction that have been built from Auguste Comte to Karl Polanyi, Marcel Mauss, and Philippe Descola. Then, I suggest to reconsidering Polanyi's typology, the most common in contemporary economic sociology, and to limit the time span to modern societies. Accordingly, it is possible to map seven forms of transaction and the related institutions at work in our societies. In conclusion, the political consequences of the existence of these different forms of transaction are highlighted. (English)
Keywords: don; exchange; gift; héritage; inheritance; marché; market; solidarity; solidarité; échange

The Return of Karl Polanyi - Somers, Margaret; Block, Fred (Dissent, 2014)
In the first half century of Dissent’s history, Karl Polanyi almost never made an appearance in the magazine’s pages. On one level this is surprising, because Polanyi was a presence in socialist circles in New York City from 1947 through the mid-1950s, the period of Dissent’s gestation. On another level it is unsurprising, in that Polanyi was a heterodox thinker—even among fellow socialists. With some significant exceptions, it has taken decades to recognize the extraordinary theoretical contributions to socialist thought that he made in his masterpiece, The Great Transformation: The Social and Political Origins of Our Time,first published in 1944.
Keywords: Vienna (Austria); democracy; economics; primacy of politics; socialism

The Power of Market Fundamentalism - Block, Fred; Somers, Margaret R. (Harvard University Press, 2014)
What is it about free-market ideas that give them tenacious staying power in the face of such manifest failures as persistent unemployment, widening inequality, and the severe financial crises that have stressed Western economies over the past forty years? Fred Block and Margaret Somers extend the work of the great political economist Karl Polanyi to explain why these ideas have revived from disrepute in the wake of the Great Depression and World War II, to become the dominant economic ideology of our time.Polanyi contends that the free market championed by market liberals never actually existed. While markets are essential to enable individual choice, they cannot be self-regulating because they require ongoing state action. Furthermore, they cannot by themselves provide such necessities of social existence as education, health care, social and personal security, and the right to earn a livelihood. When these public goods are subjected to market principles, social life is threatened and major crises ensue.Despite these theoretical flaws, market principles are powerfully seductive because they promise to diminish the role of politics in civic and social life. Because politics entails coercion and unsatisfying compromises among groups with deep conflicts, the wish to narrow its scope is understandable. But like Marx's theory that communism will lead to a "withering away of the State," the ideology that free markets can replace government is just as utopian and dangerous.
Keywords: United States history; business & economics; economic history; economic policy; economic theory; free enterprise; political economy; political science; public policy; sociology

The Rise and Fall of Ireland's Celtic Tiger: Liberalism, Boom and Bust - Ó Riain, Seán (Cambridge University Press, 2014)
In 2008 Ireland experienced one of the most dramatic economic crises of any economy in the world. It remains at the heart of the international crisis, sitting uneasily between the US and European economies. Not long ago, however, Ireland was celebrated as an example of successful market-led globalisation and economic growth. How can we explain the Irish crisis? What does it tell us about the causes of the international crisis? How should we rethink our understanding of contemporary economies and the workings of economic liberalism based on the Irish experience? This book combines economic sociology and comparative political economy to analyse the causes, dynamics and implications of Ireland's economic 'boom to bust'. It examines the interplay between the financial system, European integration and Irish national politics to show how financial speculation overwhelmed the economic and social development of the 1990s 'Celtic Tiger'.
Keywords: business & economics; economic conditions; economic development; economic history; economic policy; liberalism; political science; public policy

Le don fondateur du lien social, le cas de l'économie de marché - Lasida, Elena (Transversalités, 2014)
Le don et l’échange marchand sont généralement opposés. Pourtant, l’un et l’autre apparaissent comme fondateurs du lien social dans la mesure où l’on prend en compte la relation qu’ils créent au niveau interindividuel et collectif. Le don apparaît ainsi associé à une certaine forme de réciprocité et le marché à une certaine forme de gratuité., Gift and commodity exchange are generally opposed. But both appear as founders of the social bond when we consider the relationship they create between people and in society. The gift is thus associated with some form of reciprocity and the market with some form of gratuitousness.
Keywords: don; lien social; marché; relation; réciprocité; valeur; économie; économie sociale et solidaire

Sociology as a vocation: Moral commitment and scientific imagination - Burawoy, Michael (Current Sociology, 2014)
Public sociology and the sacrifices it entails, richly described in the case studies in this monograph, are driven by moral commitment. This is one element of sociology as a vocation. The other element is sociology as a science. The case studies are built on an embryonic sociology of commodification, understood in its historical dimensions and its global consequences. This sociology of commodification examines the disasters created by third-wave marketization and the bleak future for human existence, thereby, fueling the original moral commitment of public sociology.
Keywords: countermovement; double movement; fictitious commodities; marketization; public sociology

The Debate on Globalization and International Revitalization of Labor. A Critical Review - Fleming, Daniel; Søborg, Henrik (Nordic Journal of Working Life Studies, 2014)
This article discusses some alternative or critical theoretical contributions regarding globalization and labor. The main question in this discussion is if there are changes in direction of a possible revitalization of labor movements and if international solidarity can increase due to globalization. This question also relates to discussions of changes in division of work, the concept of work, working class, commodification, decommodification, and new centers of global production--all related to different paradigms or new concepts. The reason or need for reconceptualizing comes from the great transformation of capitalism in forms of neoliberal globalization, in a different direction than predicted by Polanyi. That is, instead of increased public sector decommodification (not profit- or market-oriented production) and national regulation, embedding capitalist markets, as seen after 1945, the last three decades have witnessed a countertransformation and large-scale recommodification by privatizing, disembedding, and deregulating global markets. As a consequence, inequality in income and working life conditions has increased in most countries and been used to press trade unions. Western industrial unions have been declining as many industries and labor-intensive, low-paid jobs moved to developing countries. Most blue-collar jobs are now in Asia, especially China, with about one-third of its employment blue collars. Is the center of global capital-labor contradictions and dynamics moving to the South, with a possibility of a new revitalization of labor and international solidarity? We discuss different optimistic and pessimistic views on a possible international revitalization of labor.
Keywords: commodification; decommodification; globalization; income distribution; international solidarity; knowledge workers; labor organizing; labour organizing; occupational citizenship; precariat; revitalization of labor; skill capture; work environment; working class; working class concept

Actualidad de la crítica de Karl Polanyi a la sociedad de mercados - Maya Ambía, Carlos Javier (Política y Cultura, 2014)
Karl Polanyi's critique of market society is a very powerful tool for understanding our current social reality. It helps us to formulate a creative and purposeful proposal that contributes to build a just, equitable, and more humane society, that would be committed to the future life on the planet. A comparison between the society criticized by Polanyi and ours, leads us to discover the validity of his basic concepts and his method for the preparation of a new critical discourse that not only takes advantage of the legacy of the author, but also expands, clarifies and updates it. (English)
Keywords: crítica social; doble movimiento; double movement; market society; mercado autorregulado; self-regulated market; social critique; sociedad de mercado

Bez zmian na „zielonej wyspie”? Kryzys ekonomiczny w polskich badaniach socjologicznych - Mrozowicki, Adam (Whither Green Island? The Global Economic crisis in Polish sociological research., 2014)
The article presents selected aspects of the discussion about the conditions and consequences of global economic crisis in Polish sociology. The author argues that the relatively limited debate on the nature of the current crisis can be explained by two factors. Firstly, it is the consequence of the dominance of modernisation paradigm in the analysis of the Polish social transformation as well as the marginalisation of two sociologies: critical labour sociology and economic sociology. Secondly, drawing on research carried out by the author on working- class life strategies in the 2000s, the limited debate is the outcome of social "normalisation" and "adaptation" to crisis experiences in the Polish society. Despite the symptoms of collective "demobilisation" in the face of successive crises, adaptation to crises has its social limits. The discourse of global economic crisis contributes to new forms of collective mobilisation in the sphere of work and politics regardless of the dominance of individualistic coping strategies inherited from the first decades of transformation. The "counter-movement" taking place in Poland is expressed in trade union radicalisation and mobilisation of radical-nationalist movements. Both processes are interpreted by the author with the reference to Karl Polanyi's work as the manifestations of self-defence of the society against the expansion of socially uncontrolled market mechanisms.
Keywords: economic crisis; neoliberalism; sociology; the myth of the market

The Pyrrhic Triumph of Finance Capital and the Return of Polanyi - Harrison, Trevor W. (Athens Journal of Social Sciences, 2014)
This paper examines the declining support for centrist parties in many western countries. Using the seminal ideas of Karl Polanyi, the paper argues this decline is attributable to the rise of neo-liberal free market policies that have resulted in widespread insecurity and led many voters to seek out political alternatives on the right and left. The paper further examines possible reasons why parties of the right, rather than the left, have been more successful at this historical juncture in channeling political disenchantment.
Keywords: countermovement; fascism; finance capital; neoliberalism

From the Apocalypse to the Revolution - Pellicani, Luciano (Telos, 2014)
The article discusses the emergence of millennialism, which is considered as one of the outcomes of the spiritual victory of Christianity over the Greco-Roman culture. The formulation of the historical-sociological category of cultural catastrophe by Hungarian economic historian Karl Polanyi is tackled. The presence of a divine messenger as one of the three elements of a messianic movement is cited. The concepts of revolutionarism, Jacobinism and Marxism are also addressed.
Keywords: Christianity; POLANYI, Karl, 1886-1964; communism; critical theory; cultural catastrophe; messianism; millennialism

The Renewal of a Critical Theory of Capitalism and Crisis – A Comment on Nancy Fraser’s Interpretation of Polanyi’s works - Deutsche Digitale Bibliothek - Sparsam,, J.; Eversberg, D.; Haubner, T.; Mader, D.; Muraca, B.; Hanno, P. (Working Paper 7/2014 of the DFG-Kollegforscher_innengruppe Postwachstumsgesellschfaten., 2014)
The paper examines Nancy Fraser’s Polanyian reading of the current capitalist crisis and her expansion of Polanyi’s notion of the ‘double movement’–social forces struggling for marketization and social protection– into a ‘triple movement’ by adding the struggle for emancipation as a third factor. In its first part, the paper reviews Fraser’s central arguments with a special focus on her reading of Polanyi’s idea of the “fictitious commodities” land, labor, and money. Second, the authors examine Fraser’s conceptualization of social forces, domination and emancipation drawing on Environmental Philosophy, Political Ecology, Marxism, Feminism, Social Philosophy as well as Polanyi himself. In the end, the paper argues that Fraser’s conception of capitalism and emancipation are in need of improvement if critical theory wants to adequately grasp the current crisis of capitalism.
Keywords: FRASER, Nancy; fictitious commodities; interpretation; triple movement